Increased Resilience of Peas Toward Root Rot Pathogens Can Be Predicted by the Nematode Metabolic Footprint - Schmidt, Jan H.; Theisgen, Leonard V.; Finckh, Maria R.; Šišić, Adnan (Frontiers in Sustainable Food Systems, 2022)
Legumes are important drivers of soil fertility, however, their frequent use in rotations fosters long-lived soil-borne pathogens that can seriously compromise legume root health and nitrogen fixation. To overcome this, the current study aims at improving the general soil suppressiveness towards pests and diseases by agroecosystem management that can be predicted by nematode-based bioindicators. Two long-term organically managed agroecosystems comparing plough and shallow non-inversion tillage were analyzed for free-living nematode communities. Soils out of these agroecosystems were evaluated further in a greenhouse assay for their ability to suppress pea root rot caused by Didymella pinodella, Fusarium avenaceum, and F. redolens. There was a general trend for higher levels of pea root rot disease severity following inoculations with single pathogens, however, this effect was heterogeneous among experiments and tillage systems. This was mainly due to an already very high resident population of D. pinodella in soil and the presence of seed-borne F. oxysporum determined by their high incidence in pea roots irrespective of the soil and inoculated pathogens. Additional inoculation with D. pinodella, for example, resulted in only 8.5% biomass reduction compared to the non-inoculated control, in both tillage systems. Similar biomass losses were recorded in non-inversion tilled soils inoculated with F. redolens. When analyzed across inoculation treatments, the pea root rot disease severity was only slightly reduced in non-inversion tilled soils when compared to the plough systems (11% in Exp 1 and, 9% in Exp 2), however in both experiments non-inversion tillage resulted in greater pea biomass (33 and 19% in Exp1 and 2, respectively). Furthermore, the metabolic, enrichment, and bacterivore carbon footprints of nematodes were 88%, 81%, and 97% higher, respectively, in the non-inversion tilled soils compared to the plough. The metabolic carbon footprint of nematodes correlated negatively with pea root rot disease severity (rho =-0.71, p = 0.047). Hence, non-inversion tillage was effective in controlling pea root rot. The use of nematode metabolic footprints for predicting soil health should be extended for various agroecosystems aiming for its general use in evaluating effects of agroecosystem management through researchers and potentially farm management advisors.